Foreign Investment on Gross Regional Domestic Product and Unemployment Rate: Political Index as Moderation - Zahrah; Nova Novriani; Hakmal Lisauda (Universitas Bumigora, 2026)
Investment plays a crucial role in driving economic growth and reducing the unemployment rate amid the current political turmoil. However, the unemployment rate declined, but the regional economy in West Nusa Tenggara decreased. This study aims to analyze how foreign investment influences the Gross Regional Domestic Product (GRDP) and the Unemployment Rate in West Nusa Tenggara. Also, the purpose is to examine how the political index affects the relationship between foreign investment and the Gross Regional Domestic Product and the Unemployment Rate. This paper used 2010-2023 data, with Foreign Investment, trade openness, and interest rate as independent variables, control variables, and a political index as a moderator, while the dependent variables are GRDP and Unemployment Rate. Three models are estimated in this study using Ordinary Least Squares (OLS). The findings are that for- eign investment has no significant effect on GRDP and Unemployment Rate in all models. However, the trade openness has significantly influenced the GRDP (in model 1) and the unemployment rate (in model 2). In addition, the political index cannot significantly weaken or strengthen the relationship between foreign investment and the GRDP, and between foreign investment and the unemployment rate. The implications of this study are that the regional government should prioritize trade and export capabilities over foreign capital to increase GRDP and employment. Also, it is necessary to optimize the business environment while maintaining political stability, which does not automatically guarantee profits from these outcomes.